BIMBINGAN KONSELING ISLAM DALAM MENGATASI PROBLEMATIKA PADA ATLET - Neni Noviza (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2015)
The problem faced by athletes in everyday life are often the cause of a person's mental disturbance in training and competing. The success of an athlete is determined by the physical and mental readiness. Since psychic or mental condition will affect their success in training and competing. Mental readiness of athletes is not only done by lifting motivation, but also other psychological aspects are needeed to be considered. Mental readiness before competing will determine the success of athletes in dealing with critical situations in the competition then discipline is absolutely necessary to achieve. But a lot of things that make someone becomes unwell both physically and mentally. For example when they have problems with his families, friends and environment around him. So, this situation influences emotional stability, concentration and energy. The role of islamic counseling for the athletes is the form of preventive where athletes get guidance or direction relating to problems preventing, such as: giving motivation, advice, in the form of a strengthening of confidence and strengthening of the attitudes of students that are not easily persued, then describe how good socialization within the scope of their fellow association, as well as to the environment due to outline the dominant environmental factors affecting the individual. The role of the guidance is given to the students before competing, the students read Al-Quran (yasinan) and pray together. This make them seem stronger and keep their spirit. While they are feeling down, they are preparing a break of one or two minutes to read Al-Fatihah, so they look more spirit again, students who had looked nervous to be more calm, it is clear that it can affect students’ life. This means that the guidance can help and coach students.